HNO3 and HCl amounts over McMurdo during the spring of 1987 - Murcray, Frank J.; Goldman, Aaron; Blatherwick, Ronald; Matthews, Andrew; Jones, Nicholas (1989)
Infrared solar spectra were obtained from the ground at McMurdo, Antarctica, during September and October 1987. Absorption features due to HNO3 and HCl have been analyzed to determine the vertical column content of these compounds for the days when observations were made. The variation of these column amounts with time is presented and discussed.